(untitled) (Journal of Partial Differential Equations, 2024)
The viability of the conformable stochastic differential equations is studied. Some necessary and sufficient conditions in terms of the distance function to K are given. In addition, when the boundary of K is sufficiently smooth, our necessary and sufficient conditions can reduce to two relations just on the boundary of K. Lastly, an example is given to illustrate our main results.